Design Prototype Robot Vacuum Cleaner Based on Arduino Microcontroller with Autonomic Mode - Herdiansya Herdiansya; Yonky Pernando (TIN: Terapan Informatika Nusantara, 2023)
The development of robotics technology in the current era has become a highly relevant need to assist humans in various everyday activities. One significant application of this technology is the creation of a prototype "Robot Vacuum Cleaner Based on Arduino Microcontroller with Autonomous Mode." This research aims to design and develop a robot vacuum cleaner capable of autonomously cleaning rooms. The design encompasses several key aspects. The physical design of the robot vacuum cleaner is an essential initial step. The shape, size, and layout of components within the robot are carefully designed to ensure easy maneuverability within the room, efficient cleaning of hard-to-reach corners, and the ability to avoid obstacles. The robot is equipped with several main components, including 3 ultrasonic sensors for obstacle detection, 3 omni wheels for excellent mobility, 2 motor drivers to control wheel movement, and 1 Arduino microcontroller as the central brain coordinating all robot operations. One of the key features of this robot is its autonomous mode. This means the robot can operate independently without human intervention. Ultrasonic sensors are used to detect obstacles around the robot. When an obstacle is detected, the robot changes direction or avoids it, allowing it to continue cleaning the room. The robot is designed to provide users with an efficient and user-friendly experience. Users only need to activate the robot, and it will perform its tasks autonomously without human intervention. This research is expected to provide significant benefits by offering an efficient solution for everyday room cleaning. The well-designed physical appearance and autonomous mode integration of this robot vacuum cleaner make it easy to use and provide a more efficient cleaning experience. Overall, this research contributes to the broader development of robotics technology in the modern era.